Global Profile: Going beyond liking to better understand product experience. (July 2019) - Spinelli, S.; Dinnella, C.; Ares, G.; Abbà, S.; Zoboli, G.P.; Monteleone, E.
Abstract: Over the last few years, interest in collecting an increasing variety of information in order to acquire a deeper and more comprehensive understanding of the consumer experience with products has steadily grown. The present study was designed to develop a methodological approach to explore the Global Profile of products within a category. A product-specific questionnaire was developed using one-on-one online interviews conducted with a modified version of the Repertory Grid Method (RGM) combined with semiotic analysis, EmoSemio, extended to cover all the main dimensions of product experience of the category of processed tomato. A 96 item questionnaire - including liking, sensory properties, emotions, emotional and functional conceptualisations and contextual appropriateness measures - was developed and employed in a home use test with 196 consumers who evaluated 9 products (one per day). All the statements were found to discriminate between products with the exception of one. A Multiple Factor Analysis showed that emotions were highly correlated with functional/emotional conceptualisations, while sensory properties were mainly related to emotional conceptualisations (memories) and uses in the recipes. The information provided by the simultaneous collection of these different dimensions allows to go beyond liking and may be used in product development and innovation in order to better understand the consumer experience of a product. Graphical abstract: Unlabelled Image Highlights: A method to develop questionnaires to study the product Global Profile is presented. The relationships among sensory properties, emotions and uses are investigated. Emotions and appropriateness of use measures supplement liking and sensory responses. Uses in cooking discriminate more than situations in a product used as ingredient.